A Touch of Culture in Learning: Teaching Materials My Food is Healthy and Nutritious for Elementary School (Cahaya Ilmu Cendekia Publisher, 2022)
Purpose of the study: This research aims to design teaching materials grounded in local wisdom and to evaluate the feasibility of these materials for the elementary/MI level, specifically focusing on Theme 9